ECONOMIC INEQUALITY IN BORDER AREAS - Lina Affifatusholihah; Iwan Ridwan Paturochman; Iis Surgawati; Fuadah Johari (CV. Adiba Aisha Amira, 2025)
The border areas of a country have strategic value to support national economic growth. This border region can serve as a point of entry for commerce and economic endeavors with adjacent nations. This has an impact on economic growth in border areas. Economic inequality is a condition where there are significant differences in the distribution of income, wealth and economic opportunities in society. Economic inequality can be the root of many social and economic problems, including poverty, unemployment, and social instability. One of the main causes of economic inequality is injustice in economic opportunities. The method used in this article is to use a literature study which contains theories related to the problem being studied. This research discusses the factors that cause economic inequality in border areas, the impact of economic inequality on people in border areas, and strategies for reducing economic inequality in border areas.